Community Structure of Bacillariophyceae in the Water of Klui Beach, North Lombok - Yuni Safrian Hadi; Lalu Japa; Lalu Zulkifli (Jurnal Biologi Tropis, 2022)
Coastal areas have potential that can be developed by the community, one of which is beach tourism. Tourism activities around that take place around the coast can affect the aquatic ecosystems especially the community structure of phytoplankton. Phytoplankton are aquatic organisms that act as primary producers. Bacillariophyceae is a class of phytoplankton that is commonly abundant in marine waters. The objectives of this study were to determine the species composition, species abundance, and community structure of Bacillariophyceae in the waters of Klui Beach. This type of research is descriptive-explorative. The Haphazard sampling was applied for determining the sampling sites. Phytoplankton data were analyzed using the abundance formula, diversity index, uniformity index, and dominance index. The results showed that the composition species of Bacilllariophyceae consisted of 48 species which included in 17 orders. Average species abundance was 298.09 ind/L (low category). The spesies diversity index was 2.37 (moderate category), the species uniformity index was 0.86 (high category), and the species dominance index was 0.13 (low category).